Lessons learned from applying established cut-off values of questionnaires to detect somatic symptom disorders in primary care: a cross-sectional study - von Schrottenberg, Victoria; Toussaint, Anne; Hapfelmeier, Alexander; Teusen, Clara; Riedl, Bernhard; Henningsen, Peter; Gensichen, Jochen; Schneider, Antonius; Linde, Klaus; Dreischulte, Tobias; Falkai, Peter; Gensichen, Jochen; et al. (Frontiers in Psychiatry, 2024)
Introduction: Based on two diagnostic accuracy studies in high-prevalence settings, two distinctly different combinations of cut-off values have been recommended to identify persons at risk for somatic symptom disorder (SSD) with the combination of the Patient-Health Questionnaire-15 (PHQ-15) and the Somatic Symptom Disorder -B Criteria Scale 12 (SSD-12). We investigated whether the reported sensitivity and specificity of both recommended cut-off combinations are transferable to primary care.Methods: In a cross-sectional study, 420 unselected adult primary care patients completed PHQ-15 and SSD-12. Patients scoring ≥9 and ≥23 (recommended cut-off combination #1) or ≥8 and ≥13 (recommended cut-off combination #2) were considered test-positive for SSD, respectively. To assess the validity of the reported sensitivity and specificity in different low to high prevalence settings, we compared correspondingly expected proportions of test positives to the proportion observed in our sample.Results: Based on combination #1, 38 participants (9%) were found to be test positive, far fewer than expected based on the reported values for sensitivity and specificity (expected minimum frequency 30% with a true prevalence ≥1%). This can only be explained by a lower sensitivity and higher specificity in primary care. For combination #2, 98 participants (23%) were test positive, a finding consistent with a true prevalence of SSD of 15% or lower. Discussion: Our analyses strongly suggest that the sensitivity and specificity estimates reported for combination #1 are not applicable to unselected primary care patients, and that the cut-off for the SSD (≥23) is too strict. Cut-off combination #2 seems more applicable, but still needs to be tested in studies that compare screening findings by questionnaires with validated diagnostic interviews as reference standard in primary care populations.